2020
DOI: 10.2147/cmar.s234618
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognosis Value of Platelet Counts, Albumin and Neutrophil-Lymphocyte Ratio of Locoregional Recurrence in Patients with Operable Head and Neck Squamous Cell Carcinoma</p>

Abstract: Background: Peripheral blood inflammation factor neutrophil-lymphocyte ratio (NLR), platelet count (PLT) and nutritional factor serum albumin (ALB) have been proposed as prognostic markers of head and neck squamous carcinoma cancer (HNSCC) in recent years. In the current study, nomogram predict models based on pre-treatment hematological parameters and a modified risk-stratified score system have been built. Methods: A total of 197 patients with oropharyngeal, hypopharyngeal and laryngeal cancers receiving mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Albumin, a protein that exerts important homeostatic effects such as maintenance of the osmotic colloid pressure, intravascular transport of molecules, lipid metabolism, thrombosis and inflammation, is classically considered as a biomarker of malnutrition and poor health status [88,89]. Hypoalbuminemia has been described as a negative prognostic factor in several diseases, [89][90][91][92]. Furthermore, low serum albumin concentrations have been shown to be associated with the severity of chronic inflammatory diseases, inflammatory bowel disease and diabetes mellitus [93], cirrhosis [94], as well as with the severity of surgical trauma [95], acute diseases [96] and sepsis [97].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin, a protein that exerts important homeostatic effects such as maintenance of the osmotic colloid pressure, intravascular transport of molecules, lipid metabolism, thrombosis and inflammation, is classically considered as a biomarker of malnutrition and poor health status [88,89]. Hypoalbuminemia has been described as a negative prognostic factor in several diseases, [89][90][91][92]. Furthermore, low serum albumin concentrations have been shown to be associated with the severity of chronic inflammatory diseases, inflammatory bowel disease and diabetes mellitus [93], cirrhosis [94], as well as with the severity of surgical trauma [95], acute diseases [96] and sepsis [97].…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin is a clinically relevant indicator of nutritional status, such as malnutrition and cachexia [3,4]. Additionally, hypoalbuminemia is often associated with systemic inflammation and impaired host immune responses [5,6]. Systemic inflammation promotes tumor progression and metastasis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other inflammatory biomarkers have also been described as prognostic factors for several malignancies such as MLR [ 10 , 11 ], PLR [ 15 , 42 ], RDW [ 12 ], MPV [ 43 ] and fibrinogen [ 12 ]. Therefore, in our study, we decided to assess the predictive ability of such inflammatory biomarkers in accurately staging the clinically negative neck, additionally to NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that changes occur across blood cell lines, and their ratios, during carcinogenesis [9]. Inflammatory blood markers like neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), platelet-lymphocyte ratio (PLR) red cell width distribution (RDW), mean platelet volume (MPV) and fibrinogen values have been described as prognostic factors for several malignancies [10][11][12][13][14][15][16][17]. Some authors have even demonstrated that NLR could play a role in predicting occult nodal metastasis in early-stage tongue tumors [3,6].…”
Section: Introductionmentioning
confidence: 99%